Hubungan Antara Waktu Tunggu Operasi pada Fraktur Collum Femur dengan Funsgional Outcome pada Pasien Berusia di atas 65 Tahun di RSUP Prof. Dr. I.G.N.G Ngoerah Denpasar pada Tahun 2021 - Tandiono, Marco; Aryana, I Gusti Ngurah Wien; Meregawa, Putu Feryawan; Maharjana, Made Agus (Universitas Udayana, 2024)
Fractures are common occurrence, especially in the elderly. One type of fracture with the most cases is neck fracture of the femur. The presence of a fracture can sometimes interfere with the body's functional activities, both before and after surgery. Different treatment times will result in varying outcomes, as in mortality and postoperative body function. This study aims to determine the relationship between waiting time for collum femur fracture surgery with functional outcome in patients who aged over 65 years. This study was an observational study with a retrospective analytic cross-sectional approach. The sampling technique used is total sampling, which by taking all available samples. Members of the research sample will be interviewed about their body's functional abilities using the Modified Harris Hip Score scoring system. The obtained interview results will be calculated and categorized. Furthermore, the data will be tested by Chi-Square Test to determine its significance. Interviews were conducted on 19 willing families. A total of 12 people underwent surgery with waiting time 5 days post-trauma, and 7 people underwent surgery with waiting time >5 days post-trauma. The results of the interviews showed that as many as 7 people died after surgery after 1 year. Meanwhile, the scoring results show that the most functional outcomes are in the bad category. The results of the Chi-Square Test showed that there was no significant difference in waiting time for surgery on post surgery outcome (p<0.05). Waiting time for surgery on collum femur fractures shows no significance on functional outcome in patients over 65 years of age.